Stop, Look, and Listen: Tips for Talking to Older Adults - Carolyn S. Wilken (EDIS)
Three simple words can help you talk to the older adults in your life: stop, look, and listen. These words are important when you are in everyday conversation. But they are even more important when you are trying to solve a problem or get essential information. It only takes a little time to stop, look, and listen. When you do, you will quickly find that you will feel less stressed. And, your older friend or family member will feel less frustrated and more understood. This document is FCS 2225, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2004.